Boganmeldelser - Ulla Bondeson; Hans-Olaf Tingleff; Bertil Ekdahl; Peter Blume; Erlendur S. Baldursson; Knud Aage Frøbert; Thordur Björnsson; Vagn Greve (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews